Preparedness of Second Batch UniSZA Medical Students towards Bedside Teaching during Clinical Posting at University Sultan Zainal Abidin - Rochman, Naim; Nor Iza, A.Rahman; Mainul, Haque (Association of Indian Pharmacist, 2015)
Introduction: Traditionally any component of medical education that takes place at the patient’s bedside is Bedside Clinical Teaching (BST). Importance of BST is absolute. Its role in developing future doctors with knowledge, skills and attitudes towards good-clinical practice is immense. BST not only improves students learning experiences but also enhances patient care. Methods: This cross-sectional study to determine the awareness and preparedness for BST in students from a new public medical school of Malaysia. Results: Study respondents 71% were female and rest 29% were male. Regardless the gender of the students, 91% of respondents take preparation before they go to BST session. Majority of them (66%) chose to go to hospital and tried to clerk patients by themselves. This research found more than half (52%) felt stressed when they are assigned for presentation of a case. Conclusions: Bedside is most essential component of medical education should be promoted to ensure proper diagnosis and management. This study thoroughly approved about the significance of bedside teaching. This cross sectional study with minimum sample size thus has its own limitations. Therefore, well designed prospective study is advocated to promote bedside teaching to ensure better health care for the common people of the world.